An ICT‐Based Mitochondria‐Targeted Fluorescent Probe for Hydrogen Peroxide with a Large Turn‐On Fluorescence Signal. Issue 4 (25th January 2019) - Liang, Xiao; Zhang, Lu; Xu, Xiaoyi; Qiao, Dan; Shen, Tangliang; Yin, Zheng; Shang, Luqing
Abstract: An ICT‐based mitochondria‐targeted fluorescent probeMito‐NP was designed and synthesized for the detection of H2 O2, with radical fluorescence intensity changes (up to 120‐fold) and a large Stokes shift (93 nm) in aqueous solution. There was good linear relationship (R 2 =0.9983) between the concentration of H2 O2 in the range of 0 to 100 μM and the fluorescence intensity at 553 nm, with a low detection limit of 0.25 μM (S/N=3).Mito‐NP could also visualize enzymatically generated H2 O2 . Furthermore, the probe could detect endogenous H2 O2 with good mitochondria targeting ability in living cells and could also detect the change in H2 O2 levels during mitochondria‐oriented apoptosis. Introduction Abstract : An ICT‐based mitochondria‐targeted fluorescent probe was designed and synthesized for hydrogen peroxide with a large turn‐on fluorescence signal in water and its bo‐imaging in living cells and it could also detect the change in H2 O2 levels during mitochondria‐oriented apoptosis.